Accuracy of ultrasound-guided core-needle biopsy confronted with pathological findings and comparison of its costs with vacuum-assisted biopsy’s costs - El-Mafarjeh, Rozan; Sonagli, Marina; Canal, Marina de Paula; Santos Filho, Eugênio César Rocha; Guatelli, Camila Souza; Santos, Silvana Soares; Graziano, Luciana; Cagnacci Neto, Renato; Souza, Juliana; Domingos, Tábata Alves; et al. (Mastology, 2020)
Introduction: Breast cancer screening has enhanced early–stage diagnosis by detection of impalpable tumors which require histopathological evaluation. Main percutaneous biopsy types are core-needle biopsy (CNB) and vacuum-assisted biopsy (VAB). CNB is less invasive and related to less bleeding and pain. VAB allows larger tissue samples and permits metal clip placement in biopsy bed for posterior localization in case of surgery. Access to VAB is restricted in Brazil due to its high costs. Objectives: To evaluate the agreement between pathological results of ultrasound (US) guided CNB with metal clip placement and surgery and settle false negative rates (FNR), sensibility, specificity, and accuracy of this method, for breast lesions < 20 mm. Methods: 388 US-guided CNB were retrospectively reviewed. Results: Surgical excision was performed in 317 patients. Overall FNR was 9.8%, (5.2% for lesions 10–20 mm), sensibility 90.2% (94.8% for lesions 10–20 mm), specificity 94.9% (94.1% for lesions 10–20 mm), and accuracy 91.1% (94.7% for lesions 10–20 mm). Cost of VAB varies from 2.2 to 12.5 times US-guided CNB. With metal clip placement, VAB costs 1.95 to 5.2 times US-guided CNB. Conclusions: For lesions that can be identified in US, CNB with metal clip placement has high sensitivity, specificity, and accuracy, as well as low FNR.